2017
DOI: 10.15835/buasvmcn-asb:12646
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Beebread – Review

Abstract: Beebread is a product of the hive obtained from pollen collected by bees, to which they add honey,digestive enzymes and subsequently is stored in the combs. The bees transform the bee pollen in beebread by an anaerobic fermentation process.A proper hive management promotes beebread collection, aimed at marketing it for human consumption since it can be considered a valuable food supplement due to its content of a wide range of nutrients. Its value is given by the content in protein, amino acids, fatty acids, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
1
50
0
2
Order By: Relevance
“…Additional information from narrative or nonclinical reviews was summarized in Supporting Information C (Campos et al, 2010;Capozzi & Lello, 2018;Denisow & Denisow-Pietrzyk, 2016;Komosinska-Vassev et al, 2015;P.F. Guine, 2015;Saraiva, Cunha, Léllis, & Nunes, 2018;Urcan et al, 2017;Xi et al, 2018). Interesting evidence from a narrative review recommends the use of a purified grass pollen extract in combination with other products like royal jelly to improve vasomotor symptoms and quality of life in premenopausal and postmenopausal women (Capozzi & Lello, 2018).…”
Section: Efficacy Of Orally Administered Pollen For Nonallergic Dismentioning
confidence: 99%
See 2 more Smart Citations
“…Additional information from narrative or nonclinical reviews was summarized in Supporting Information C (Campos et al, 2010;Capozzi & Lello, 2018;Denisow & Denisow-Pietrzyk, 2016;Komosinska-Vassev et al, 2015;P.F. Guine, 2015;Saraiva, Cunha, Léllis, & Nunes, 2018;Urcan et al, 2017;Xi et al, 2018). Interesting evidence from a narrative review recommends the use of a purified grass pollen extract in combination with other products like royal jelly to improve vasomotor symptoms and quality of life in premenopausal and postmenopausal women (Capozzi & Lello, 2018).…”
Section: Efficacy Of Orally Administered Pollen For Nonallergic Dismentioning
confidence: 99%
“…In two reviews including clinical studies, it was underscored that bee pollen may protect the cardiovascular system by lowering lipid levels and platelet aggregation and stabilize visual acuity in patients with atherosclerotic disease (Denisow & Denisow-Pietrzyk, 2016;Komosinska-Vassev et al, 2015). Evidence from three reviews also indicated that bee pollen and bread may be valid nutritional supplements for frail subjects like postsurgical patients or long-hospitalized elderly people (Campos et al, 2010;Denisow & Denisow-Pietrzyk, 2016;Urcan et al, 2017). Moreover, limited evidence suggests that bee bread might be useful for patients with anemia (Campos et al, 2010).…”
Section: Efficacy Of Orally Administered Pollen For Nonallergic Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Information on bee bread as one of the bee products is overlooked with more highly acclaimed honey [1]. Acquisition of bee bread can be troublesome for some bee farmers because it requires the destruction of the bee hive for harvesting [2]. us, most studies were conducted on bee pollen of the honeybee Apis mellifera whereby bee pollen was obtained through the pollen trap installed at the bee hive's entrance.…”
Section: Introductionmentioning
confidence: 99%
“…Often regarded as byproduct, pot-pollen are usually neglected by the farmers due to the lack of knowledge in harvesting and preservation method for pot-pollen. This is a wastage as they have high nutritive value as it contain high level of proteins, carbohydrates, lipids, vitamins and phenolic compounds [11]. Previous research on pot-pollen has shown that their extract contains antioxidant [12], besides having antibiotic and antimicrobial properties [12], [13].…”
Section: Introductionmentioning
confidence: 99%